Functionalized carbon microfibers (biomass-derived) ornamented by Bi2S3 nanoparticles: an investigation on their microwave, magnetic, and optical characteristics. (18th November 2020) - Peymanfar, Reza; Moradi, Fereshteh
Abstract: The biomass-derived materials emerged as novel, low-cost, green, and light-weight microwave absorbers. On the other hand, the sulfide nanostructures due to narrow band gap demonstrated significant dielectric features. In this research, the pure carbon microfibers were prepared using Erodium cicutarium harvest and they were functionalized by a sonochemistry method. The treated microfibers were coated by Bi2 S3 nanoparticles, obtained by a novel modified solvothermal route. X-ray powder diffraction, Fourier transform infrared, diffuse reflection spectroscopy, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy, and vector network analyzer analyses were applied to characterize the features of the prepared structures. The obtained results manifest that the anchoring nanoparticles onto the functionalized microfibers narrowed band gap to 1.35 eV and reinforced polarizability of the nanocomposite, desirable for dielectric attenuation. In this study, the interfacial interactions were modulated using polyacrylonitrile (PAN) and polyvinylidene fluoride. Interestingly, FCMF blended in PAN demonstrated an eye-catching efficient bandwidth as wide as 8.13 GHz (RL > 10 dB) with only 2.00 mm in thickness, whereas it illustrated an outstanding reflection loss of 81.96 at 11.48 GHz with a thickness of 2.50 mm. More significantly, FCMF/Bi2 S3 /PAN nanocomposite promoted the efficient bandwidth to 3.07 GHz (RL > 20 dB). Noteworthy, all of the samples illustrated total electromagnetic interference shielding effectiveness (SET ) more than 15 dB entire the x and ku-band frequency.